Mortality Profile of COVID-19 Co-Infection in HIV/AIDS Patients at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia - Januarti, Catur Ifda; Rusli, Musofa; Nugraha, Jusak; Puspitasari, Dwiyanti (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2025)
Highlights: The majority of HIV/AIDS patients who succumbed to the effects of co-infection at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, were of productive age, with the predominant complications being anemia and bacterial infections. Tuberculosis was listed as the most common opportunistic infection that exacerbated the condition of HIV/AIDS patients and caused death during the ongoing pandemic of COVID-19.   Abstract Introduction: Human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) is an immune system disease caused by the HIV infection, making individuals susceptible to various diseases, including coronavirus disease (COVID-19). Co-infection in HIV/AIDS patients can worsen the severity of the diseases, especially in those with comorbidities, complications, and opportunistic infections, potentially leading to death. This study aimed to determine the mortality profile of COVID-19 co-infection in HIV/AIDS patients at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, from January 2020 to December 2022. Methods: This study employed a descriptive cross-sectional method, utilizing secondary data from 48 medical records of COVID-19 co-infection in HIV/AIDS patients at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, from January 2020 to December 2022, collected through a total sampling technique. Results: Of the 105 total HIV/AIDS patients with COVID-19 co-infection, 48 were selected in this study based on predefined inclusion and exclusion criteria. The mortality profile showed a predominance of males (75%), with an average age of 36.5 years. The most common comorbidity was bacterial infection (38.6%), with the highest complication being anemia (55.6%), and the most prevalent opportunistic infection being tuberculosis/TB (50%). Conclusion: The mortality profile of COVID-19 co-infection in HIV/AIDS patients indicated a higher occurrence among males, with an average age of 36.5 years old. The most common comorbidity was bacterial infection, whilst the most prevalent complications include anemia, with TB being the most frequent opportunistic infection.